2015
DOI: 10.1007/s00228-015-1880-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the accumulation of prophylactic dosages of low-molecular-weight heparins (LMWHs) in patients with renal insufficiency

Abstract: PurposeAlthough therapeutic dosages of most low-molecular-weight heparins (LMWHs) are known to accumulate in patients with renal insufficiency, for the lower prophylactic dosages this has not been clearly proven. Nevertheless, dose reduction is often recommended. We conducted a systematic review to investigate whether prophylactic dosages of LMWH accumulate in renal insufficient patients.MethodsA comprehensive search was conducted on 17 February 2015 using Embase, Medline, Web of Science, Scopus, Cochrane, Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 60 publications
1
53
0
3
Order By: Relevance
“…In addition, LMWHs are successful in the prevention and treatment of thromboembolism. [6,[13][14][15][16][17][18][19][20][21][22][23][24][25] They are more effective than UFH in venous thromboembolism (VTE) and non-Q wave myocardial infarction. Routine heparin therapy in this setting is still under debate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, LMWHs are successful in the prevention and treatment of thromboembolism. [6,[13][14][15][16][17][18][19][20][21][22][23][24][25] They are more effective than UFH in venous thromboembolism (VTE) and non-Q wave myocardial infarction. Routine heparin therapy in this setting is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21] Da Pozzo et al [3] reported that bemiparin provided a significant decrease, as shown by the reduction of endothelial cell tubule network, while both fondaparinux and UFH did not show any significant effect on in vitro angiogenesis. One major finding of this study is that bemiparin was the only drug to show inhibited angiogenesis in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Применение далтепарина натрия не сопровождается биоаккумуляцией и не требует коррекции профилактиче-ской дозы [18,19].…”
unclassified